Gambaran Resiliensi pada Istri Korban Covid-19 - Aniyatuzzulfah, Aniyatuzzulfah; Febriyanti, Dianita; Fadli, Nadia Alfiyyatus Sholihah; Ningrum, Ardana Reswari Miranda; Nuqul, Fathul Lubabin (Journal of Islamic and Contemporary Psychology, 2022)
Covid-19 occurred in 2019-2021 made many deaths in around the world. Therefore, many families have lost their members. Losing family members will result in grief and role changes. This study aimed to reveal a picture of the resilience experienced by wives who lost their husbands died due to exposure to Covid-19. This study uses Qualitative method with a Phenomenological Strategy, involving a 29-year-old as a respondent or subject. The results show descriptions of a strong effort from subject as a wife which suffering a lost husband to get out of adiscard difficult situation. Self-esteem, spirituality, and positive emotions are factors owned by the wife to achieve a resilient itself. The external support factors as External factors that support are children's presence and support from people around, such as family and friends.